Beslut om betydande miljöpåverkan för järnvägsprojekt - Löfgren, Hannes (SLU/Dept. of Urban and Rural Development, 2009)

(untitled)
This thesis examines the reasons to why railway projects conducted by Banverket (Swedish National Rail Administration) could be expected to cause significant effects on the environment, on which grounds the County Administrative Board and Swedish National Rail Administration base their decisions/assumptions and highlight regional differences between the different Swedish national rail administrations regions. Total 24 railway projects, conducted or being conducted, during the time period 2001 - January 2010 have been analyzed and studied. These projects represent eight different measures/activities which are dispersed throughout all five of the Swedish National Rail Administration´s different regions. Swedish legislations demands that the planner of a new railway project shall first conduct a pre-study and then conduct a public consultation which provides the participants an opportunity to provide input. The County Administrative Board shall then decide if the project could cause significant effects on the environment. The amount of published material is scarce regarding why railway projects cause significant effects on the environment.